HOW DOES PAIR WORK IMPROVE THE SPEAKING FLUENCY OF INTERMEDIATE IELTS STUDENTS AGED 17-22 IN AN EFL CLASSROOMS - Gulamjanova Mutabar Farxadovna; Komilova Nozima Tulanbaevna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This study examines how pair work enhances the speaking fluency of intermediate IELTS learners aged 17–22 in an EFL classroom. Drawing on communicative language teaching and task-based learning, it uses an action research design to identify effective pair activities and explore the role of motivation. Data were collected over four weeks through teacher reflections, student journals, and recorded speaking tasks. Insights from Kamolova et al. (2025) on technology integration informed the use of gamified pair tasks. Findings show that structured pair work significantly increases participation and speaking output. Peer interaction also supports lower-level learners by improving confidence. The study offers practical recommendations for implementing pair work in IELTS-focused classrooms.